Tackling grand challenges with projects: Five insights and a research agenda for project management theory and practice. Issue 6 (August 2022) - Ika, Lavagnon A.; Munro, Lauchlan T.
Highlights: Essay suggests five insights for tackling grand challenges projects. Essay proposes ten questions for research on grand challenge project behavior. Essay outlines peculiarities of grand challenge projects. Essay posits selectionism and instructionism are worthwhile approaches. Essay argues collaborative rationality trump linear rationality. Abstract: The project management field has two blind spots: a focus on "run-of-the-mill" projects at the expense of pioneering "push-the-envelope" projects and a rigor-relevance gap in the research. There are simply too few scholarly works devoted to project management and grand challenges, those wicked, complex, uncertain, messy, boundary-crossing problems that confront the world. Drawing on the grand challenges of sustainable development and COVID-19 and the projects they provoke, this essay highlights five insights for theory and practice and suggests that selectionism and instructionism are worthwhile approaches, while collaborative rationality may trump linear rationality. We argue that project management for grand challenges is a promising land of "push-the-envelope" portfolios that can help overcome these two blind spots, regain relevance, avoid anomia, and revitalize theory and practice. To this end, we show that there is a concomitant need for a theory of grand challenge project behavior and offer an agenda for future research.